MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI METODE PEMBERIAN TUGAS (TASK BASE) SISWA KELAS V SEKOLAH DASAR NEGERI 02 RUMBAI PEKANBARU - Usman, Raja (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The Giving Task Methode is a an efision method In the class, Special to readingcomprehension clas, and invite class. The purpose og this research is to analysis somemethod giving tas toincreasc Reading Comprehension to Fifth Grade in Elemntrary School02 Rumbai Pekanbaru.In the research the student into group and each group is givin two texts white different topix.The students asked to read, look for main idea, support ide, suppose imformation and writeconclusion, then write the answers in the work book (LKS) has been prepared by teachers.The first cycle, there are many tudent don’t bring books but the second cycle have change,for example In te student who don’t bring books and don’t give attention to the teacher can’twe find again. It has been remembered by teachers.The research has done two seklus. In the first cycle the studens can’t do all their task,answer the question because the student still write the texts as the aswer, The students stillwrite the text as the aswer. The students who don’t get good mark fifteen students (66,56%)and get good mark are twelve students (44,44%). In the second cycle the increase mark ofstudent can we found that is the 100%. Students pass of the test and the down mark iseighty five and the high mark 1 is ninety five, t’s is course by process of learning which haveknoen by the teacher, How to way increase of student comprehension in the read havechanged. In the first and the seconf cycle, all the activities student and teachers in thecomprehension of learning have increased.